Assessment of the immunoexpression profile of breast ductal carcinoma with Cyclin D1, Her-2/Neu and p53 at Yangon General Hospital, Myanmar - Tun, Khin Darli; Ko, Min Ko; Arumugam, Sudha; Chakravarthi, Srikumar; Vejayan, Jaya (Nepalese Journal of Cancer, 2021)
One hundred cases of histologically proven invasive ductal carcinomas were histologically graded based on modified Bloom and Richardson Grading. Out of these 17 cases each of low grade, intermediate grade, and high grade invasive ductal carcinomas were selected for Immunostaining using the monoclonal antibodies Cyclin D1,pP53 and Her2/neu. It was found that for all three monoclonal antibodies the lowest histological grade of Invasive Ductal Carcinoma of the Breast showed the lowest positivity with Cyclin D1 ( 11.76%) and p53 ( 17.64%) and Her2/neu ( 47.05%). The intermediate grade tumour showed ( 70.58% ) positivity with Cyclin D1 and 58.58 % in p53 and Her2/neu. The high grade invasive ductal carcinoma of the breast showed the highest positivity of Cyclin D1 (76.47%) , p53 (88.24% ) ,Her2/neu ( 94.12% ); These suggest that Cyclin D1 , P53 and Her2/neuimmunoexpression positivity increases with rising histological grades of invasive ductal carcinoma of breast.